Effect of oral clonidine premedication on perioperative hemodynamic response for patients undergoing abdominal surgeries under general anaesthesia - Ajmani, Tejinder Singh; Pareek, Somya (Journal of Neonatal Surgery, 2025)
Background: Premedication enhances patient outcomes by minimizing anxiety, stabilizing hemodynamics, and improving perioperative recovery. Clonidine, an alpha-2 adrenergic agonist, has shown promise in anesthesia for its sedative, sympatholytic, and analgesic properties. Aim: To evaluate the perioperative effects of a single oral dose of clonidine (150 mcg) on hemodynamic responses, sedation, anesthetic requirements, and postoperative recovery in patients undergoing elective abdominal surgery under general anesthesia. Methods: A prospective, randomized, controlled clinical study was conducted on 50 ASA I–II patients aged 20–60 years. Patients were divided into two groups: Group A received oral clonidine (150 mcg) and Group B received a placebo (Vitamin C) 90 minutes prior to surgery. Hemodynamic parameters, sedation scores (Ramsay Sedation Score), and Rate Pressure Product (RPP) were recorded at multiple perioperative time points. Volatile anesthetic requirements and adverse events were also assessed. Statistical analysis was performed using Student’s t-test and z-test for proportions. Results: Group A demonstrated significantly lower pulse rates, RPP, and better perioperative hemodynamic stability compared to Group B. The hemodynamic response to laryngoscopy, intubation, and surgical stimuli was significantly blunted in the clonidine group. Higher sedation scores were observed preoperatively in Group A. Postoperative nausea, vomiting, and shivering were less frequent in Group A, although incidences of bradycardia and hypotension were higher but manageable. Conclusion: Oral clonidine (150 mcg) is an effective premedication agent that provides superior sedation, attenuates hemodynamic responses, reduces anesthetic requirements, and enhances surgery.